The level of H2O2 type oxidative stress regulates virulence of Theileria‐transformed leukocytes. (21st October 2013) - Metheni, Mehdi; Echebli, Nadia; Chaussepied, Marie; Ransy, Céline; Chéreau, Christiane; Jensen, Kirsty; Glass, Elizabeth; Batteux, Frédéric; Bouillaud, Frédéric; Langsley, Gordon
Summary T heileria annulata infects predominantly macrophages, and to a lesser extent B cells, and causes a widespread disease of cattle called tropical theileriosis. Disease‐causing infected macrophages are aggressively invasive, but this virulence trait can be attenuated by long‐term culture. Attenuated macrophages are used as live vaccines against tropical theileriosis and via their characterization one gains insights into what host cell trait is altered concomitant with loss of virulence. We established that sporozoite infection of monocytes rapidly induces hif1‐α transcription and that constitutive induction of HIF‐1α in transformed leukocytes is parasite‐dependent. In both infectedmacrophages and B cells induction of HIF‐1α activates transcription of its target genes that drive host cells to perform Warburg‐like glycolysis. We propose that Theileria‐infected leukocytes maintain a HIF‐1α‐driven transcriptional programme typical of Warburg glycolysis in order to reduce as much as possible host cell H2O2 type oxidative stress. However, in attenuated macrophages H2O2 production increases and HIF‐1α levels consequently remained high, even though adhesion and aggressive invasiveness diminished. This indicates that Theileria infection generates a host leukocytes hypoxic response that if not properly controlled leads to loss of virulence.